Multidisciplinary Management of Pediatric Hepatoblastoma: A 20-Year Single-Center Experience - Tayfun Küpesiz, Funda; Akınel, Ayşe Nur; Akbaş, Hilal; Sivrice, Çiğdem; Tüysüz Kintrup, Gülen; Karagüzel, Güngör; Melikoğlu, Mustafa; Gelen, Mustafa Tekinalp; Aydınlı, Bülent; Küpesiz, Alphan; Güler, Elif (Turkish Journal of Gastroenterology, 2022)
Background: Hepatoblastoma is rare cancer that responds well to risk-based chemotherapy, and surgical treatment is needed to achieve complete remission and satisfactory survival rates in hepatoblastoma patients. In this study, we evaluated the clinical features and treatment outcomes of pediatric hepatoblastoma patients treated in our clinic. Methods: Eighteen patients with hepatoblastoma who were treated and followed up in our center between June 1999 and June 2020 were analyzed retrospectively. All patients were evaluated by a multidisciplinary team and managed using a risk-based protocol (SIOPEL-1 and SIOPEL-3). Results: The patients’ mean age at diagnosis was 38.33 ± 52.34 months. Sixteen patients (89%) received neoadjuvant chemotherapy, and 2 patients (11%) who underwent complete mass excision at diagnosis received adjuvant chemotherapy. After neoadjuvant therapy, the tumor was completely resected in 8 patients (45%), while liver transplantation was performed in 6 patients (34%) because complete resection of the tumor was not possible. Two patients died before surgical treatment. One patient relapsed with lung metastasis after salvage chemotherapy. She is alive without disease at 64 months. The mean follow-up time was 59.3 ± 49.8 months; 5-year overall and disease-free survival rates were 88.9% and 80.8%, respectively. The 5-year overall survival rate was 100% for both liver transplant and resected patients, whereas 5-year disease-free survival was lower in transplant patients (75% vs 100%, P < .001). Conclusion: Multidisciplinary follow-up is especially important for patients who may need liver transplantation. Some patients may benefit from new treatment options such as radiofrequency ablation and cyberknife treatment. Cite this article as: Tayfun Küpesiz F, Akınel AN, Akbaş H, et al. Multidisciplinary management of pediatric hepatoblastoma: A 20-year single-center experience. Turk J Gastroenterol. 2022;33(12):1069-1078.